SKRINNING FITOKIMIA EKSTRAK ETANOL DAUN JERUK PURUT (Citrus hystrix) DARI KABUPATEN KLATEN - Fadilah Qonitah; Reni Ariastuti; Ahwan; Pratiwi Maharani, Nurul Astia Wuri (GEMA, 2022)
Kaffir lime leaves are used for traditional medicine and cosmetic ingredients. Phytochemical screening aims to provide information related to the class of compounds contained in the ethanol extract of kaffir lime leaves. The extraction process uses the maceration method with ethanol 96%. The components contained in the extract were analyzed by their compounds by colour test (qualitative) with several reagents for flavonoids, saponins, tannins, terpenoids, steroids, alkaloids, and essential oils. The results of the phytochemical screening test showed that the ethanol extract of kaffir lime leaves contained a class of flavonoid compounds, saponins, tannins, triterpenoids, alkaloids and essential oils